2012
DOI: 10.3109/10715762.2012.660527
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin and catechin synergistically inhibit angiotensin II-induced redox-dependent signalling pathways in vascular smooth muscle cells from hypertensive rats

Abstract: Dietary flavonoids, present in different amount in foods, are associated with the prevention of hypertension, but little is known about the interactions between them. The aim of this study was to explore the effect of quercetin (Q), catechin (C) and the mixture, on Angiotensin II (AngII)-induced redox-dependent signalling pathways and cell behaviour. Mesenteric smooth muscle cells (MesSMC) from spontaneously hypertensive rats (SHR) were incubated with AngII (0.1 μmol/L) alone, or with the mixture of low concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 34 publications
(6 reference statements)
1
7
0
Order By: Relevance
“…Some in vitro studies have shown a synergistic effect of C and Q on the inhibition of collagen‐induced platelet aggregation and platelet adhesion . C and Q also synergistically inhibit angiotensin II induced redox‐dependent signaling pathways in vascular smooth muscle cells from hypertensive rats , while no synergistic effects were observed in pulmonary vascular smooth muscle . Other study that evaluated the antiproliferative effects of Q, C, and epicatechin in three different cancer cell lines showed that only Q possesses antiproliferative activity , suggesting that these compounds may have different mechanisms of action.…”
Section: Discussionmentioning
confidence: 99%
“…Some in vitro studies have shown a synergistic effect of C and Q on the inhibition of collagen‐induced platelet aggregation and platelet adhesion . C and Q also synergistically inhibit angiotensin II induced redox‐dependent signaling pathways in vascular smooth muscle cells from hypertensive rats , while no synergistic effects were observed in pulmonary vascular smooth muscle . Other study that evaluated the antiproliferative effects of Q, C, and epicatechin in three different cancer cell lines showed that only Q possesses antiproliferative activity , suggesting that these compounds may have different mechanisms of action.…”
Section: Discussionmentioning
confidence: 99%
“…The phytochemical analysis of MMEAF revealed the presence of different phenolic compounds that have protective vascular effects, which could additively and/or synergistically contribute to the effects of this fraction on aorta from obese rats. Studies have shown that polyphenolic mixtures present synergistic and additive antioxidant and vascular effects [ 76 , 77 , 78 , 79 ]. In this respect, quercetin and kaempferol synergistically acted in the reduction in H 2 O 2 -induced oxidative stress [ 80 ].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, some studies have shown that quercetin antagonizes Ang II‐induced apoptosis of human umbilical vein endothelial cells as well as myocardial hypertrophy . In addition, quercetin has also been reported to regulate the proliferative and migratory response of VSMCs during Ang II‐induced hypertension …”
Section: Discussionmentioning
confidence: 99%